BIOMECHANICAL AND KINETOTHERAPEUTICAL ASPECTS OF THE SCAPULO-HUMERAL PERIARTHRITIS SYNDROME - Florentina NECHITA (Editura Universitatii Transilvania din Brasov, 2019)
The scapulo-humeral periarthritis is the clinical syndrome characterized by pain, joint redness and functional impotence determined by pathological processes located at the shoulder level and affecting the periarticular structures: ligaments, joint capsule, tendons, and muscles. The form of the scapulo-humeral periarthritis successfully benefits from treatment of stabilization and biomechanical and neuromuscular balancing, in kinetotherapy applications. In conclusion, in the recovery of the scapulohumeral periarthritis, the kinetotherapeutic treatment intervenes to prevent loss of mobility and prevent fibrosis, restoring muscle strength, stability and controlled movements of the shoulder.